Fragile X-Associated Tremor/Ataxia Syndrome: From Molecular Pathogenesis to Development of Therapeutics - Kong, Ha Eun; Zhao, Juan; Xu, Shunliang; Jin, Peng; Jin, Yan (Frontiers in Cellular Neuroscience, 2017)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is a neurodegenerative disorder caused by a premutation CGG repeat expansion (55-200 repeats) within the 5’ UTR of the fragile X gene (FMR1). FXTAS is characterized by intension tremor, cerebellar ataxia, progressive neurodegeneration, parkinsonism, and cognitive decline. The development of transgenic mouse and Drosophila melanogaster models carrying an expanded CGG repeat has yielded valuable insight into the pathophysiology of FXTAS. To date, we know of two main molecular mechanisms of this disorder: (1) a toxic gain of function of the expanded CGG-repeat FMR1 mRNA, which results in the binding/sequestration of the CGG-binding proteins and (2) CGG repeat-associated non-AUG-initiated (RAN) translation, which generates a polyglycine peptide toxic to cells. Besides these CGG-mediated mechanisms, recent studies have shed light on additional mechanisms of pathogenesis, such as the antisense transcript ASFMR1, mitochondrial dysfunction, DNA damage from R-loop formation, and 5-hydroxymethylcytosine (5hmC)-mediated epigenetic modulation. Here we summarize the recent progress towards understanding the etiology of FXTAS and provide an overview of potential treatment strategies.